Biodegradable bags for the production of plant seedlings - Bilck,Ana Paula (2014)
The production of plant seedlings has traditionally used polyethylene bags, which are thrown out in the soil or burned after transplant because the large amount of organic material attached to the bags makes recycling difficult. Additionally, when a seedling is taken from the bag for transplant, there is the risk of root damage, which compromises the plants development. In this study, we developed biodegradable bags to be used in seedling production, and we verify their influence on the development of Brazilian ginseng (Pfaffia glomerata (Spreng) Pedersen), when the plant is planted without being removed from the bag. Both black and white biodegradable bags remained intact throughout the seedling production period (60 days). After being transplanted into containers (240 days), they were completely biodegraded, and there was no significant difference between the dry mass of these plants and that of plants that were transplanted without the bags. The plants that were cultivated without being removed from the polyethylene bags had root development difficulties, and the wrapping showed no signs of degradation. The use of biodegradable films is an alternative for the production of bags for seedlings, as these can then be transplanted directly into the soil without removing the bag, reducing the risk of damage to the roots during the moment of transplant.